The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41586-021-03430-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating eligibility criteria of oncology trials using real-world data and AI

Abstract: Line of therapy (LoT); confidence interval (CI); first line of therapy (1L); second line of therapy (2L). Extended Data Table 2 | Validation on progression-free survival hazard ratioThe number of inclusion and exclusion criteria, the number of eligible patients and the hazard ratio of progression-free survival with confidence interval of emulated aNSCLC trials with eligibility criteria under three scenarios: original criteria of the clinical trial, fully relaxed criteria and data-driven criteria learned from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 38 publications
0
121
0
Order By: Relevance
“…In a recent study from Liu et al (32) which aims at evaluating ECs for oncology trials using RWD and AI, the authors quantified the representability of each study trait with SHAP (33), and they tried to relax the range of each EC for broadening the participation. Only traits with continuous values are considered in a one-by-one manner.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Liu et al (32) which aims at evaluating ECs for oncology trials using RWD and AI, the authors quantified the representability of each study trait with SHAP (33), and they tried to relax the range of each EC for broadening the participation. Only traits with continuous values are considered in a one-by-one manner.…”
Section: Discussionmentioning
confidence: 99%
“…This point would require more diverse clinical trials. To this end, a study using RWD from the US Nationwide oncology data source Flatiron Health showed that when using RWD to emulate clinical trials in lung cancer, removing many common trial exclusion criteria had a minimal effect on the trial effect estimate [14]. Relaxing trial entry criteria; however, had an important benefit of making clinical trials more inclusive for women and older patients.…”
Section: Rwd Facilitating Considerations Of Equitymentioning
confidence: 99%
“…Moreover, by combining protein modeling and molecular dynamics simulations, nonconservative substitutions in functional regions of the spike glycoprotein of SARS-CoV-2 were demonstrated to contribute to differences in its virulence [109]. In spite of being potentially useful in the present "pandemic contingency", AI will undoubtedly prove useful in the future to design novel clinical trials with more inclusive molecular eligibility criteria in cancer patients [110].…”
Section: Immuno-oncology Approaches Beyond Just Checkpoint Inhibition -Cancer Vaccines and Oncolytic Virusesmentioning
confidence: 99%